Highly active zinc-finger nucleases by extended modular assembly - Bhakta, Mital S.; Henry, Isabelle M.; Ousterout, David G.; Das, Kumitaa Theva; Lockwood, Sarah H.; Meckler, Joshua F.; Wallen, Mark C.; Zykovich, Artem; Yu, Yawei; Leo, Heather; Xu, Lifeng; Gersbach, Charles A.; et al. (Genome Research, 2013)
Zinc-finger nucleases (ZFNs) are important tools for genome engineering. Despite intense interest by many academic groups, the lack of robust noncommercial methods has hindered their widespread use. The modular assembly (MA) of ZFNs from publicly available one-finger archives provides a rapid method to create proteins that can recognize a very broad spectrum of DNA sequences. However, three- and four-finger arrays often fail to produce active nucleases. Efforts to improve the specificity of the one-finger archives have not increased the success rate above 25%, suggesting that the MA method might be inherently inefficient due to its insensitivity to context-dependent effects. Here we present the first systematic study on the effect of array length on ZFN activity. ZFNs composed of six-finger MA arrays produced mutations at 15 of 21 (71%) targeted loci in human and mouse cells. A novel drop-out linker scheme was used to rapidly assess three- to six-finger combinations, demonstrating that shorter arrays could improve activity in some cases. Analysis of 268 array variants revealed that half of MA ZFNs of any array composition that exceed an ab initio B-score cutoff of 15 were active. These results suggest that, when used appropriately, MA ZFNs are able to target more DNA sequences with higher success rates than other current methods.
10.1101/gr.143693.112